(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The present scientific article investigates phraseological units containing the lexeme «water» within English, Uzbek and Russian linguacultures, highlighting both similarities and differences in their usage and cultural significance. Phraseological units, or idiomatic expressions, often reflect the values, beliefs, and practices of a culture, making them a rich area for linguistic and cultural study. The research investigates a variety of phrases across the languages, analyzing their meanings, contexts, as well as the metaphorical implications of water as a natural element.